2007
DOI: 10.1097/wnn.0b013e31802b6c0b
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic Assessment of Patients With Advanced Parkinson Disease Submitted to Extradural Motor Cortex Stimulation

Abstract: In this patient group, EMCS, an experimental neurosurgical treatment, had a positive effect on motor symptoms. Neuropsychologic assessment after a 1-year follow-up period showed that cognitive functions had not changed with respect to baseline characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Instead of being worried about their weight, anorexic males usually present more 'muscularity concerns' and body dissatisfaction. Also, they tend to over-exercise to increase their muscle mass compared to AN females, who focus on leanness-oriented exercises [21]. These gender-related differences in the AN phenotype likely depend on multiple factors (e.g., hormonal, genetic, socio-cultural and psychological differences) but both male and female anorexic patients warrant a multidisciplinary work-up.…”
Section: Anorexia Nervosa (An)mentioning
confidence: 99%
“…Instead of being worried about their weight, anorexic males usually present more 'muscularity concerns' and body dissatisfaction. Also, they tend to over-exercise to increase their muscle mass compared to AN females, who focus on leanness-oriented exercises [21]. These gender-related differences in the AN phenotype likely depend on multiple factors (e.g., hormonal, genetic, socio-cultural and psychological differences) but both male and female anorexic patients warrant a multidisciplinary work-up.…”
Section: Anorexia Nervosa (An)mentioning
confidence: 99%
“…A wide stimulation area also may be important for wide cortical stimulation for Parkinson disease, essential tremor, and pain (4,17,18,28). These applications may be further developed based on rechargeable battery technology.…”
Section: Multiple and Wider Targetsmentioning
confidence: 99%
“…Preliminary observations in PD patients treated by EMCS suggest that electrical stimulation of the primary motor cortex (PMC) may modulate neural activity in the basal ganglia (BG), by activating cortico-BG projections 1,3 , resulting in slight improvement of Parkinsonian motor symptoms, especially axial motor symptoms 4,5 . The effects of EMCS on cognitive functioning in patients with PD remain to be clarified 5,6 . In PD patients treated by bilateral EMCS, comparisons between preoperative and postoperative cognitive performance on neuropsychological tasks did not detect any significant overall cognitive decline at a 6-month 5 and 1-year postoperative follow-up 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of EMCS on cognitive functioning in patients with PD remain to be clarified 5,6 . In PD patients treated by bilateral EMCS, comparisons between preoperative and postoperative cognitive performance on neuropsychological tasks did not detect any significant overall cognitive decline at a 6-month 5 and 1-year postoperative follow-up 5,6 . One study showed at 3-month postoperative assessment a significant but transient decline of performance (increased execution time) only on the Stroop interference test, a task assessing response inhibition and sensitive to frontal lobe dysfunction 5 .…”
Section: Introductionmentioning
confidence: 99%